Cultural Intertextuality in Piramerd's Poems (Raparin Journal of Humanities (RJH), 2025)
This study explores the intertextual dimensions of culture in the poetry of Piramerd, who is a significant figure in the Kurdish literature.  This study takes an in-depth look at the Kurdish poet Piramerd, examining the way his poems introduce readers with different cultural Intertextuality of culture. The interaction between texts has become a major turning point in the intellectual and interpretation of literary works in Kurdish literary criticism, so that the strength of the concept was able to create a positive reading among poets, which led to innovation and introduction of new literary works. Due to the fact that, Piramird made use of culture in many of his texts; Therefore, this type of Intertextuality is more common, which marks a turning point in Kurdish literary. This is evident of the poet's rich background in the use of cultural words and codes.     The main objectives of this research are to identify the types of cultural differences in Piramird's poetic works (Theory and Practice) In order to reveal the results that cultural distortions have given a special and obvious stamp to the poems and intensively culture has reflected on the works of the old man. Itself, stage) using the sections (folklore, proverbs, riddles, jokes and satire, stories and adventures, poems and songs).